Population-scale study of eRNA transcription reveals bipartite functional enhancer architecture - Kristjánsdóttir, Katla; Dziubek, Alexis; Kang, Hyun Min; Kwak, Hojoong (Nature communications, 2020)
Enhancer RNAs (eRNA) are unstable non-coding RNAs, transcribed bidirectionally from active regulatory sequences, whose expression levels correlate with enhancer activity. We use capped-nascent-RNA sequencing to efficiently capture bidirectional transcription initiation across several human lymphoblastoid cell lines (Yoruba population) and detect ~75,000 eRNA transcription sites with high sensitivity and specificity. The use of nascent-RNA sequencing sidesteps the confounding effect of eRNA instability. We identify quantitative trait loci (QTLs) associated with the level and directionality of eRNA expression. High-resolution analyses of these two types of QTLs reveal distinct positions of enrichment at the central transcription factor (TF) binding regions and at the flanking eRNA initiation regions, both of which are associated with mRNA expression QTLs. These two regions—the central TF-binding footprint and the eRNA initiation cores—define a bipartite architecture of enhancers, inform enhancer function, and can be used as an indicator of the significance of non-coding regulatory variants. Enhancer RNAs are transcribed bidirectionally from core transcription initiation regions. Here, by employing nascent RNA sequencing, the authors identify quantitative trait loci (QTLs) associated with enhancer RNA level and directionality, revealing the bipartite architecture of enhancers.